If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 3y = 4 Solving 10x + 3y = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 10x + 3y + -3y = 4 + -3y Combine like terms: 3y + -3y = 0 10x + 0 = 4 + -3y 10x = 4 + -3y Divide each side by '10'. x = 0.4 + -0.3y Simplifying x = 0.4 + -0.3y
| 2y^2-6y=10 | | 2/7m-1/7=3/14 | | 14-n=8 | | n=8y+5p | | log[4]x-log[4](2x-4)=3 | | 3^7/3^5= | | 2(x-5)-4=6-4(4+x) | | 5r+4+4=-4+r | | 100-8x-20=72 | | q^2+12q+49=0 | | 2ln(x-1)=ln(5x) | | 30x+2=15 | | 9log(3x)=45 | | 24=(3x-2)(x+3) | | -20.4r+4(1+5)=4.8 | | 6ln(4x)+3=15 | | 24=(3x-2)+(x+3) | | 2(15)+2=15 | | -6+v/2=11 | | -6.2p+3(-2+2p)=-4.6 | | 8+B=11 | | 7200=120000+90000x | | 2y^3-y^2-5y-2=0 | | x+(x*.16)=46000 | | x+(xy)=46000 | | 8/12=36/x | | 15.5y-13.7y=-26 | | y=-.25*(x-8)-1 | | 12*50= | | 6x+6z=7+5y | | -20+18t=-(6t-4) | | 5x+7z=2+7y |